Pollution levels and risk assessment of heavy metals in sediment at Tengi River, Selangor / Za Akimi Mohd Zainuddin ... [et al.]. - Mohd Zainuddin, Za Akimi; Mohd Saidi, Nadasofa; Abdul Rahman, Ahmad Taufek; Nik Ariffin, Nik Azlin; Md Yunus, Sabarina (Universiti Teknologi MARA, Negeri Sembilan, 2024)
The pollution levels and impact of heavy metal (HM) contamination distribution caused by human activities on mangroves, rivers, estuaries, and coastal wetlands have recently gained attention. Waste discharged from agricultural runoff may increase pollution due to rapid population growth and socioeconomic development in Tanjung Karang, Selangor, areas such as boat manufacturing factories, residential areas, and port development, as well as waste discharged from agriculture runoff. As a result, anthropogenic radioactive materials could accumulate in sediments and infiltrate the food chain, affecting the natural system and directly endangering human health. This study determined the concentrations of heavy metals (Fe, As, Pb, Cu, and Cd) and radionuclides (Th-232, U-238, and K-40) in Tengi River sediment from 15 locations were collected using a PVC tube and Energy Dispersive X-ray Fluorescence Spectrometer (EDXRF). As a result, Cu (68.00-127.64 mg/kg), Pb (86.84-147.62 mg/kg), Fe (9.11-14.24 mg/kg), As (78.24-97.74 mg/kg), and Cd (0.11-10.02 mg/kg) while the average concentrations of radionuclides are Th>K>U with 91.96 mg/kg, 42.77 mg/kg, and 13.34 mg/kg, respectively. The data obtained were used to estimate pollution levels (Igeo, EF, CF, and PLI) using Sediment Quality Assessment (SQA) and to evaluate the potential impact of human activities on the ecosystem by calculating the Ecological Risk Index of Heavy Metals. The results show that the concentration of heavy metals and radionuclides in surface sediment may be caused by human activities near the study area. Igeo, CF, PLI, and ER indicated a heavy metal load with As and Cd in surface sediments, while Cu and Pb had a minimal degree. To conclude, Cu < Pb < Cd < As from ecological risk, As and Cd are most polluted in the surface sediment along the down streams of the river.